Network security first-step - Thomas, Thomas M. (Cisco Press, 2004)
Your first step into the world of network security No security experience required Includes clear and easily understood explanations Makes learning easy Your first step to network security begins here! Learn about hackers and their attacks Understand security tools and technologies Defend your network with firewalls, routers, and other devices Explore security for wireless networks Learn how to prepare for security incidents Welcome to the world of network security! Computer networks are indispensable-but they're also not secure. With the proliferation of Internet viruses and worms, many people and companies are considering increasing their network security. But first, you need to make sense of this complex world of hackers, viruses, and the tools to combat them. No security experience needed! Network Security First-Step explains the basics of network security in easy-to-grasp language that all of us can understand. This book takes you on a guided tour of the core technologies that make up and control network security. Whether you are looking to take your first step into a career in network security or are interested in simply gaining knowledge of the technology, this book is for you!
Includes index. - Print version record
Keywords: Computer networks -- Security measures; Réseaux d'ordinateurs; Sécurité; Mesures; Computer networks; Security measures